Knowledge-guided automatic thresholding for 3-dimensional display of head MRI images - Suzuki, H.; Toriwaki, J. (Pattern Recognition, 9th International Conference on, 1988: Proceedings, 2003)
A segmentor is described which automatically extracts soft tissues from the multisliced magnetic resonance imaging (MRI) of the head region by an iterative thresholding procedure. 3-D graphic displays are shown of the segmented soft tissues. To get the optimum threshold value, a goodness measure is used based on the knowledge of the object.< >